(untitled) (Research, Society and Development, 2020)
Agile methodologies were born as a more flexible response to older methods of software development, that were more focused on planning than on interactions. In parallel, there is an evolution of the quality of the developed software, considering systems requirements such as user interaction, usability and accessibility. In this way, a systematic literature review was carried out aiming to identify the attention given to accessibility in software development in writings about agile methods, identifying how accessibility has been worked with agile software development methods. The research could find some studies in several areas of the software life cycle, such as development processes, accessibility assessment methods and accessibility refactoring, which show that although research in this area is still incipient, it has evolved considerably in the last decade.